Reactions of selected bean pure lines and accessions to Meloidogyne species - Mullin, BA; Abawi, G.S.; Pastor Corrales, Marcial A.; Kornegay, Julia L. (Scientific Societies, 1991)
Over 150 bean (Phaseolus vulgaris) pure lines and accessions were evaluated in growth chamber and greenhouse trials for reactions to one or more populations of root-knot nematodes (Meloidogyne spp.) collected from Colombia or the United States. Bean pure lines and accessions were evaluated for root galling severity and nematode egg mass production on a 1 9 scale, where 1 = no root galling or no egg mass production and 9 = 76 100% of root system galled or >100 egg masses per root system. A resistance index (RI) was generated for each pure line or accession by combining the root galling severity and nematode egg mass production ratings such that RI = (root galling severity rating2 + egg mass production rating2). Reaction classes were defined as immune (RI = 2), highly resistant (RI = 3 8), resistant (RI = 9 18), moderately resistant (RI = 19 32), intermediate (RI = 33 50), moderately susceptible (RI = 51 72), susceptible (RI = 73 98), and highly susceptible (RI = 99 162). Only about 30 bean lines and accessions had a response of moderately resistant or better (RI <33) to the populations of Meloidogyne spp. used. Among those highly resistant to root-knot nematodes were A 211, Carioca, Manoa Wonder, Nemasnap, and PI 313709. These pure lines and accessions can be used as valuable parental materials in the development of root-knot-resistant bean cultivars adapted for Colombia, Peru, and other countries.